Analisis Faktor Kunci dan Tantangan dalam Pemenuhan Standar Keselamatan dan Kesehatan Kerja (K3) untuk Mencapai Infrastruktur yang Berkualitas: Sebuah Literatur Review - Farida, Ery; Sholihah, Qomariyatus; Andarini, Sri; Natsir, M. Halim (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
he construction sector is a dynamic industry that produces projects in terms of infrastructure and buildings. This sector faces challenges, particularly in worker safety and health (K3) in every project. Statistics show that the increase in fatalities and permanent disability cases due to accidents at construction sites in Indonesia is among the highest compared to other industrial sectors. This study examines the key factors and challenges in meeting occupational safety and health (K3) standards to achieve quality infrastructure. The method used in this study is a literature review conducted through databases such as PubMed, Science Direct, and Google Scholar. After selection, 42 articles were used as sources for analysis in this study. The results indicate that technical aspects, both Internal Risks and Project Risks, are the most influential causes of health and safety risks in a building construction project. Meanwhile, External Non-Technical Risks are the least influential causes of health and safety risks in a building construction project. Risk control can be carried out through good working methods, the use of tools according to warning signs, the appropriate use of personal protective equipment (PPE), and clear explanations of accident risks and risk control methods by the contractor.